The role of transportation in regional economic development : a Charles River Associates research study - Kraft, Gerald; Meyer, John Robert; Valette, Jean-Paul. (Lexington, etc. : D. C. Heath and Co., 1971)
The purpose of this study is to determine to what extent economists have answered the question of whether, how and by how much transportation affects regional development
Includes bibliographical references
osc 08/03/2019
Loans
Keywords: Economic Developmet; Transportation